A rare case of Baker's cysts with hematoma of the lower calf treated with arthroscopic internal drainage combined with intramuscular dissection - Wenbin Luo; Ao Wang; Hairui Zhang; Zhiyao Zhao; Ye Zhang; Xiaoning Liu (Heliyon, 2024)
Popliteal cysts, also termed Baker's cysts, are clinically common cystic lesions in the popliteal fossa. Typically, the contents of a ruptured cyst tend to spread into the myofascial interfaces in any direction, most commonly inferomedially or into a palpable superficial position. However, to our knowledge, reports of Baker's cysts dissecting into the deep intermuscular septum of the lower calf are extremely rare. We present here the details of the successful treatment through arthroscopy combined with lower calf incision of a patient who sustained hematoma of the knee and lower calf secondary to Baker's cyst rupture. Given the rarity of this disease in China, we present this case report to improve our understanding of the disease and avoid misdiagnosis and provide evidence for its clinical treatment, management, and prognosis.